Transatlantic divide : comparing American and European society - Martinelli, Alberto (Oxford University Press, 2007)
"The book describes, interprets, and analyzes the key features of European society and American society and major social trends in the United States and in the European Union in the last 50 years. The United States of America and the European Union are the two strongest economic powers in the contemporary world, roughly equivalent in terms of GNP, market size and scientific potential, but asymmetrical in terms of political influence and military might. The US and the EU can be both seen as successful examples of economic development and of political and cultural modernization. But they have followed different paths to reach such a position. They can be considered as two variants of Western modernity."--Book cover